2008
DOI: 10.1007/s10495-008-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

The tubulin-depolymerising agent combretastatin-4 induces ectopic aster assembly and mitotic catastrophe in lung cancer cells H460

Abstract: The relationship between microtubular dynamics, dismantling of pericentriolar components and induction of apoptosis was analysed after exposure of H460 non-small lung cancer cells to anti-mitotic drugs. The microtubule destabilising agent, combretastatin-A4 (CA-4) led to microtubular array disorganization, arrest in mitosis and abnormal metaphases, accompanied by the presence of numerous centrosome-independent "star-like" structures containing tubulin and aggregates of pericentrosomal matrix components like ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…These drug exposures are relevant for in vivo studies, where mouse plasma levels of the active CA4P metabolite CA4 were reported in the region of 0.5-2.8 lM, within 90 min of administering 100 mg/kg CA4P. 29,43 Our data confirmed several previous studies [24][25][26][27][28] showing that the mode of direct tumor cell death was anti-proliferative, leading to apoptosis, and that resistance to CA4P was indeed maintained in vivo, since markers of apoptosis, namely DNA fragmentation and cleaved caspase-3 expression were significantly greater in SW1222…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These drug exposures are relevant for in vivo studies, where mouse plasma levels of the active CA4P metabolite CA4 were reported in the region of 0.5-2.8 lM, within 90 min of administering 100 mg/kg CA4P. 29,43 Our data confirmed several previous studies [24][25][26][27][28] showing that the mode of direct tumor cell death was anti-proliferative, leading to apoptosis, and that resistance to CA4P was indeed maintained in vivo, since markers of apoptosis, namely DNA fragmentation and cleaved caspase-3 expression were significantly greater in SW1222…”
Section: Discussionsupporting
confidence: 90%
“…Previous in vitro studies have shown CA4P-mediated cytotoxicity to be a result of mitotic arrest and apoptosis. [26][27][28] Tumor cell apoptosis was examined in both lines following treatment with CA4P for 24 hr. Consistent with the tumor cell viability data, the SW1222…”
Section: The Sw1222mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, 4 and a combretastatin derivative induced mitotic catastrophe dependent on spindle checkpoint and caspase-3 activation in non-small cell lung cancer cells [33,34]. Mitotic catastrophe has also been demonstrated for 4 and related derivatives in both human endothelial cells (HUVEC) and human lung carcinoma cells (H460) [35].…”
Section: Antiproliferative Activity In Breast Cancer Cellsmentioning
confidence: 87%
“…Another possible cause of spindle multipolarity is the presence of multiple centrosomes that can be formed by centrosome fragmentation or duplication (31,32). It has been reported that loss of centrosome integrity in association with multipolar spindle formation can be induced by different chemical agents, including estrogens (33), combretastatin (34), rotenone (35), and arsenite (36). 4-Oxo-4-HPR-induced multipolar spindles exhibited only two centrosomes, which were visualized by γ-tubulin staining.…”
Section: Discussionmentioning
confidence: 99%